2016
DOI: 10.4049/jimmunol.1500747
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin Modulates Allergic Airway Inflammation by Attenuating CCL20-Mediated Dendritic Cell Recruitment

Abstract: Recruitment and activation of dendritic cells (DCs) in the lungs are critical for Th2 responses in asthma, and CCL20 secreted from bronchial epithelial cells (BECs) is known to influence the recruitment of DCs. Because asthma is a disease that is closely associated with oxidative stress, we hypothesized that clusterin, an oxidative stress regulatory molecule, may have a role in the development of allergic airway inflammation. The aim of this study was to examine whether clusterin regulates CCL20 production fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 46 publications
(44 reference statements)
0
32
0
Order By: Relevance
“…The study suffers from the referral bias from the sampled population and the lack of phenotype classification but provides an additional piece of evidence that chronic inflammation in response to infection may underlie the development of PD (Bower et al, 2006). Taken the emergent role of ApoE (Zhang et al, 2011;Gonzalez et al, 2017), clusterin (CLU) (Falgarone and Chiocchia, 2009;Hong et al, 2016), triggering receptor expressed on myeloid cells 2 (TREM2) in innate immunity (Fahrenhold et al, 2018;Jay et al, 2015;Shi and Holtzman, 2018), and their convergence as risk variants for sporadic AD, it is likely that an altered inflammatory response to exogenous substances in the airways is transferred through the olfactory neuroepithelium to the connected olfactory circuitry. This is supported by the increased infections incidence of viruses in ApoEε4 carriers (HSV-1, HIV1, Hepatitis C, Hepatitis B) (Itzhaki et al, 1997;Burgos et al, 2006;Finch and Morgan, 2007;Burt et al, 2008;Hishiki et al, 2010;Yin et al, 2010) and bacteria (C. Pneumoniae, Gram negative bacteria) (de Bont et al, 1999;Van Oosten et al, 2001;Kattan et al, 2008).…”
Section: Olfactory Gateway Of Peripheral To Central Inflammatory Respmentioning
confidence: 99%
“…The study suffers from the referral bias from the sampled population and the lack of phenotype classification but provides an additional piece of evidence that chronic inflammation in response to infection may underlie the development of PD (Bower et al, 2006). Taken the emergent role of ApoE (Zhang et al, 2011;Gonzalez et al, 2017), clusterin (CLU) (Falgarone and Chiocchia, 2009;Hong et al, 2016), triggering receptor expressed on myeloid cells 2 (TREM2) in innate immunity (Fahrenhold et al, 2018;Jay et al, 2015;Shi and Holtzman, 2018), and their convergence as risk variants for sporadic AD, it is likely that an altered inflammatory response to exogenous substances in the airways is transferred through the olfactory neuroepithelium to the connected olfactory circuitry. This is supported by the increased infections incidence of viruses in ApoEε4 carriers (HSV-1, HIV1, Hepatitis C, Hepatitis B) (Itzhaki et al, 1997;Burgos et al, 2006;Finch and Morgan, 2007;Burt et al, 2008;Hishiki et al, 2010;Yin et al, 2010) and bacteria (C. Pneumoniae, Gram negative bacteria) (de Bont et al, 1999;Van Oosten et al, 2001;Kattan et al, 2008).…”
Section: Olfactory Gateway Of Peripheral To Central Inflammatory Respmentioning
confidence: 99%
“…Treg cells are consistently detected in NPC biopsies (Lau et al, ; Yip, Abdullah, Yusoff, & Seow, ). In addition to recruitment of DCs (Hong et al, ), CCL20/CCR6 axis mediates the migration of in CD4(+) FOXP3(+) regulatory T cells (Tregs) into inflammatory tissues (Cook et al, ; Zhang, Kang, & Zhao, ). Expression of CCL20 is positively correlated with Treg markers (FoxP3 and IL‐10) in multiple human cancers (Frick et al, ; Liu et al, ; Zhang, Qi, et al, ).…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…CCL20 belongs to the CC chemokine subfamily and is ligand for CCR6 (Lee, Phan, Hulett, & Korner, 2015) and is a direct target gene of NF-κB (Ignacio, Kabir, Lee, Adunyah, & Son, 2016). CCL20 is known to influence the recruitment of DCs (Hong et al, 2016).…”
Section: Nf-κb Signaling Links Ebv-mediated Chronic Inflammation Wimentioning
confidence: 99%
“…It has also been indicated that CCL11 and CCL20 are produced following IL-4 or IL-13 stimulation (25). Furthermore, it has been demonstrated that clusterin induces the production of CCL20 by regulating the oxidative stress environment in airway epithelial cells from mice studies (26). Previous studies have demonstrated that microRNA-34a, 15-lipoxygenase and histamine are important regulators for CCL22 in airway epithelial cells (27)(28)(29).…”
Section: Expression Properties Of Epithelial Chemokinesmentioning
confidence: 99%
“…C-C chemokine receptor CCR6, IL-33R and TSLPR (corresponding receptors for CCL20, IL-33 and TSLP respectively) are expressed on immature DCs (iDCs). By binding with these receptors, CCL20, IL-33 and TSLP activate iDCs and promote their maturation (26,42). DCs then migrate to the T cell zone in mediastinal lymph nodes, where they activate T cells via antigen presentation and co-stimulation.…”
Section: Functional Properties Of Chemokines and Associations Betweenmentioning
confidence: 99%